2001
DOI: 10.1046/j.1365-2664.2001.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of provenance on the performance of Crataegus monogyna in hedges

Abstract: Summary 1.Grants for wildlife enhancement in the British Isles have supported the widespread planting of new hedges along field margins. However, much of the planted material, particularly of hawthorn Crataegus monogyna , has been obtained from the continental mainland of Europe. There is a need to assess the implications of this practice for hedgerow performance and for the conservation of indigenous genetic variation. 2. One local ecotype and eight commercial provenances (four British and four continental Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…The resulting planting stock may be less well adapted to the regional growing conditions (e.g. JONES et al, 2001). Especially in Flanders, largescale planting of non-autochthonous provenances of native woody species can be a threat for relict autochthonous populations.…”
Section: An Alarming Situationmentioning
confidence: 99%
“…The resulting planting stock may be less well adapted to the regional growing conditions (e.g. JONES et al, 2001). Especially in Flanders, largescale planting of non-autochthonous provenances of native woody species can be a threat for relict autochthonous populations.…”
Section: An Alarming Situationmentioning
confidence: 99%
“…For example, provenance trials of trees and shrubs showed that stock of British origin is better adapted to British conditions than continental stock (e.g. Jones, Hayes, & Sackville Hamilton 2001;Worrell 1992). Here we use the term 'local' as a synonym for autochthonous, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Boshier and Stewart 2005;Savolainen et al 2007) and similar studies of woody species with no relevant economic importance are largely lacking in many parts of Europe including Flanders, although a few examples do exist (e.g. Crataegus monogyna: Jones et al 2001). In the absence of long-term provenance tests, putative local adaptation can be addressed by an assessment of intraspecific differentiation in populations both at the genetic and phenotypic level.…”
Section: Introductionmentioning
confidence: 95%